How priming exercise affects oxygen uptake kinetics: from underpinning mechanisms to endurance performance - Goulding, R. P.; Burnley, M.; Wüst, R. C. I. (Sports Medicine, 2023)
The observation that prior heavy or severe-intensity exercise speeds overall oxygen uptake (V?O2) kinetics, termed the "priming effect", has garnered significant research attention and its underpinning mechanisms have been hotly debated. In the first part of this review, the evidence for and against (1) lactic acidosis, (2) increased muscle temperature, (3) O2 delivery, (4) altered motor unit recruitment patterns and (5) enhanced intracellular O2 utilisation in underpinning the priming effect is discussed. Lactic acidosis and increased muscle temperature are most likely not key determinants of the priming effect. Whilst priming increases muscle O2 delivery, many studies have demonstrated that an increased muscle O2 delivery is not a prerequisite for the priming effect. Motor unit recruitment patterns are altered by prior exercise, and these alterations are consistent with some of the observed changes in V?O2 kinetics in humans. Enhancements in intracellular O2 utilisation likely play a central role in mediating the priming effect, probably related to elevated mitochondrial calcium levels and parallel activation of mitochondrial enzymes at the onset of the second bout. In the latter portion of the review, the implications of priming on the parameters of the power-duration relationship are discussed. The effect of priming on subsequent endurance performance depends critically upon which phases of the V?O2 response are altered. A reduced V?O2 slow component or increased fundamental phase amplitude tend to increase the work performable above critical power (i.e. W´), whereas a reduction in the fundamental phase time constant following priming results in an increased critical power.